Cyber Surveillance and Privacy Issues vis-à-vis International Law - Walia, Ivneet Kaur (Brawijaya Law Journal, 2023)
The ‘Big Brother is Watching’, is now a trend that is prevalent in the society where the unregulated and unfiltered monitoring of data and interception has led to interference with the privacy rights of the individuals. The background to the concept may not be expressly seen in text but the context of privacy be protected can be seen in legal instruments such as United Nations Declaration on Human Rights, International Covenant on Civil and Political Rights. Though, the legal jurisprudence has also taken sides for placing community interest over individual interest but has often been deficient in providing objective reasonings and justifications. When the privacy and the human rights are interfered with, no one but the State should own the responsibility. The contours of this responsibility have been circumscribed by the existing international legal instruments, but their effectiveness is compromised because of their non-binding characteristics. The paper outlines the importance of regulating mass surveillance, secret surveillance, cyber espionage, cyber attacks etc. and has facilitated a discussion of establishing a pattern of standardized norms in line with human rights obligations catalyzed by cyber diplomacy, which can easily be adopted by States. The paper is Analytical and descriptive in nature. The question will always be debatable when it comes to States exercising their right of surveillance for maintaining law and order and upholding the security of the nation being violative of individual rights. So, whether the States are able to strike a balance between State authority and Fundamental rights of the individuals? Whether the proportionality that is exhibited is justifiable? The uncontrollable parasitic attack on digital communications, without reasonable suspicion is excessive, arbitrary and abusive. There is a need not only for a structured legal framework but also procedural safeguards, oversight mechanisms and redressal forums.